2007
DOI: 10.1016/j.jhep.2007.02.020
|View full text |Cite
|
Sign up to set email alerts
|

Liver-specific HBsAg transgenic mice are over-sensitive to Poly(I:C)-induced liver injury in NK cell- and IFN-γ-dependent manner

Abstract: Background/Aims: The role of natural killer (NK) cells in the development of hepatitis B virus (HBV)-associated liver injury remains obscure. In this study, we elucidated the role of NK cells in liver injury of HBsAg transgenic mice (HBs-B6), a mimic of human healthy chronic HBsAg carriers, triggered by polyinosinic:polycytidylic acid [Poly(I:C)].Methods: HBs-B6 or wild B6 mice were intraperitoneally injected with Poly(I:C) at different doses. Liver injury was evaluated by serum transaminase activity and histo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 52 publications
0
41
1
Order By: Relevance
“…Treatment with IFN-γ in vitro triggered much higher activation of downstream signals (pSTAT1-IRF-1) in hepatocytes from HBs-B6 mice. Depletion of Kupffer cells and neutralization of endogenous IL-12 did not affect poly(I : C)-induced over-sensitive liver injury in HBs-B6 mice [14] . It was also found that a low dose of ConA, non-toxic when given to wild-type mice induced severe liver injury in HBs-Tg mice, which was dependent on accumulated intrahepatic natural killer (NK) cells.…”
Section: Innate Recognition Mediates the Overreactive Immune Liver Inmentioning
confidence: 77%
“…Treatment with IFN-γ in vitro triggered much higher activation of downstream signals (pSTAT1-IRF-1) in hepatocytes from HBs-B6 mice. Depletion of Kupffer cells and neutralization of endogenous IL-12 did not affect poly(I : C)-induced over-sensitive liver injury in HBs-B6 mice [14] . It was also found that a low dose of ConA, non-toxic when given to wild-type mice induced severe liver injury in HBs-Tg mice, which was dependent on accumulated intrahepatic natural killer (NK) cells.…”
Section: Innate Recognition Mediates the Overreactive Immune Liver Inmentioning
confidence: 77%
“…The innate immunopathogenesis responsible for the susceptibility to hepatocyte injury in chronic HBV carriers was examined. HBs-Tg mice were over-sensitive to Poly I:C induced liver injury, which was absolutely dependent on the presence of NK cells and IFN-γ produced by intrahepatic NK cells [105] . A low dose of ConA, non-toxic when given to wild type mice induced severe liver injury in HBs-Tg mice, which was dependent on accumulated intrahepatic NK cells.…”
Section: Interaction Among Hepatic Immune Cells In Liver Inflammationmentioning
confidence: 98%
“…HBV and HCV are noncytopathic viruses in the hepatocytes, and thus immunologically mediated events play an important role in the pathogenesis and outcome of these infections. The innate immune responses including NK cells, invariant NKT cells and non-classical NKT cells have been reported to contribute to the pathogenesis of liver disease or viral clearance in the infections [51,52,55,58,105] . The innate immunopathogenesis responsible for the susceptibility to hepatocyte injury in chronic HBV carriers was examined.…”
Section: Interaction Among Hepatic Immune Cells In Liver Inflammationmentioning
confidence: 99%
“…Pre-activation of T cells aggravates poly I : C-induced liver injury by up-regulating NK cell function [75]. HBs-transgenic mice are over-sensitive to poly I : C-induced liver injury, which is dependent on the presence of NK cells and IFN- produced by intrahepatic NK cells [76,77]. In primary biliary cirrhosis (PBC), stimulation with ligands for TLR3 and TLR4 enhanced NK cellmediated cytotoxicity against biliary epithelial cells (BECs), during which IFN- produced by TLR3 ligand-stimulated monocytes enhances the cytotoxicity of TLR4 ligand-activated NK cells [78].…”
Section: Tlr Signaling On Nk Cell Activationmentioning
confidence: 99%